The Analysis of Social Wellbeing Indicators in the Context of Russian Economy Structural; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Zhironkin S. A. Sergey Aleksandrovich (2016, 2016)
Title screen